Sochi Olympics legacy in mass sport and healthy lifestyle development and popularization - V. A. Badtieva; I. V. Uryeva; A. V. Kvitchasty; N. V. Sichinava; R. R. Glukhova; E. V. Koroleva (Спортивная медицина: наука и практика, 2020)
The Olympic Games are a mega-event not only for athletes, coaches and referees. It is also very important for all citizens of the Olympic Games host country. The Olympics legacy is the development of mass rather than professional sport. Six years passed since Sochi Olympics and now it is time to evaluate and analyze the intangible aspect of the mega-sports event legacy. We analyzed the data on the overall growth in the number of people systematically involved in physical education and sports in Russia from 2008 to 2019. The study findings suggest a significant positive impact of the Olympics on people’s lifestyle. Over the decade, the number of people involved in physical education and sports in Russia increased 2.5 times. The main positive effect is revealed in young people.